The Influence of Previous Year’s Audit Opinion and Operational Complexity on Audit Report Lag with the Audit Committee as a Moderating Variable - Ekawati, Putri; Annisa, Dea (Journal Development Manecos, 2026)
Timely audited financial reporting is essential for ensuring the relevance and reliability of financial information for investors and other stakeholders. However, delays in the completion of external audits remain a recurring issue among Indonesian listed companies, particularly within the energy sector, which is characterized by complex organizational structures and operational activities. This study examines the effects of the previous year’s audit opinion and operational complexity on Audit Report Lag (ARL), while also investigating whether the audit committee moderates these relationships. The study employs a quantitative associative approach using panel data from 54 energy sector companies listed on the Indonesia Stock Exchange during the 2020–2024 period, resulting in 270 firm-year observations. Secondary data were obtained from audited annual reports and financial statements, and the hypotheses were tested using panel data regression with Moderated Regression Analysis (MRA). Model selection procedures, including the Chow, Hausman, and Lagrange Multiplier tests, identified the Fixed Effect Model as the most appropriate estimation model. The findings indicate that neither the previous year’s audit opinion nor operational complexity significantly affects Audit Report Lag. Furthermore, the audit committee, measured by the number of committee members, does not moderate the relationships between the independent variables and Audit Report Lag. These findings suggest that audit completion is influenced more by firm-specific characteristics and current audit conditions than by historical audit outcomes or organizational complexity. They also indicate that audit committee size alone is insufficient to represent governance effectiveness in accelerating audit completion. This study contributes to the Audit Report Lag literature by providing evidence from the Indonesian energy sector using a panel data approach that controls for unobserved firm-specific heterogeneity. Future research is encouraged to employ multidimensional measures of operational complexity and audit committee effectiveness to provide a more comprehensive understanding of the determinants of audit timeliness.